Abstraction, witnessing, and repair; or, how multimodal research can destabilize the coloniality of the gaze. Issue 3 (September 2021) - Welcome, Leniqueca A; Thomas, Deborah A
The recent renewal of attention to abstraction within Black literary and visual studies, it seems to us, has to do with an interest in the various ways abstraction rejects ascribed categories, eschews narrow assumptions about "relevance, " and embraces experimentation during a moment when it is arguably most needed. Abstraction moves us simultaneously outside of representative realism, and it embraces research practices that often require the kind of intimacies that have long been the bread and butter of anthropology. As multimodal ethnographers, we have long made our ethical commitments to interlocutors through embodied participation and collective knowledge production. In this essay, we attend to questions of abstraction, witnessing, and refusal within our own filmic and photographic practices addressing state violence in the Caribbean. We are interested in the spatio-temporality of both witnessing and refusal and in the relationships between form and audience. We are interested in how forms of abstraction capture the ephemeral, performative, affective, non-linear, and unpredictable ways something that feels like sovereignty circulates and is transmitted from one to another, without contributing to a process of overexposure or a desire for transparency.